2021
DOI: 10.1007/s00167-021-06464-4
|View full text |Cite|
|
Sign up to set email alerts
|

Robotic-arm assisted total knee arthroplasty is associated with improved accuracy and patient reported outcomes: a systematic review and meta-analysis

Abstract: This systematic review and meta-analysis were conducted to compare the accuracy of component positioning, alignment and balancing techniques employed, patient-reported outcomes, and complications of robotic-arm assisted total knee arthroplasty (RATKA) with manual TKA (mTKA) and the associated learning curve. Searches of PubMed, Medline and Google Scholar were performed in October 2020 using PRISMA guidelines. Search terms included “robotic”, “knee” and “arthroplasty”. The criteria for inclusion were published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 58 publications
5
66
0
2
Order By: Relevance
“…Furthermore, postoperative coronal alignment parameters were all comparable between the groups. In addition to the numerous published studies on improved alignment accuracy in primary robotic-assisted knee arthroplasty in comparison to conventional TKA [ 12 , 19 , 23 , 26 , 31 ], this case series was able to demonstrate a comparable accuracy and outcome to robotic-assisted primary knee arthroplasty. Intraoperative control of component alignment and joint line restoration in revision arthroplasty is often a challenge due to further bone loss or loss of bony reference points after implant removal.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Furthermore, postoperative coronal alignment parameters were all comparable between the groups. In addition to the numerous published studies on improved alignment accuracy in primary robotic-assisted knee arthroplasty in comparison to conventional TKA [ 12 , 19 , 23 , 26 , 31 ], this case series was able to demonstrate a comparable accuracy and outcome to robotic-assisted primary knee arthroplasty. Intraoperative control of component alignment and joint line restoration in revision arthroplasty is often a challenge due to further bone loss or loss of bony reference points after implant removal.…”
Section: Discussionmentioning
confidence: 67%
“…Robotic-assisted primary TKA (RA-TKA) is increasingly gaining popularity in the orthopaedic domain [ 9 ]. The main advantages of RA-TKA include improved component alignment and real-time control of soft tissue balance [ 12 , 19 , 23 , 26 , 31 ]. The use of RA-TKA in the context of UKA revision is a promising approach to improve the results of these revision procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Balanced gaps have been considered a prerequisite for good function and endurance in TKA, and a balanced knee could affect clinical outcomes [ 22 ]. Moreover, this precision and intraoperative feedback on the gap balancing could possibly minimize limitations in the conventional techniques and sizing options [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hozack et al found that patients undergoing RATKA had significantly higher functional activity scores at 6 weeks and 1 year postoperatively [67]. A meta-analysis done by Zhang et al included seven clinical studies that reported functional outcomes when comparing RATKA using different robotic devices to conventional TKA [68]. Different outcome scores were utilized across the included studies, with the KSS being the most reported followed by Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores.…”
Section: Clinical and Patient-reported Outcomes After Tkamentioning
confidence: 99%